Functional imaging and modelling of the heart : 9th International Conference, FIMH 2017, Toronto, ON, Canada, June 11-13, 2017, Proceedings /: 9th International Conference, FIMH 2017, Toronto, ON, Canada, June 11-13, 2017, Proceedings. (2017) - Unknown
No abstract available